The role of management and leadership in the schooling of at-risk learners: a case study of a school in Namibia - Ipinge, Emma (Rhodes University, Faculty of Education, Department of Education, 2004)
Most schools that serve learners who come from disadvantaged areas and backgrounds face unusually difficult challenges. These schools experience poor performance and disciplinary problems, and teachers lack motivation and commitment. This study explores the role of leadership and management in the schooling of at-risk learners at Pandu Primary School. This school accommodates learners mostly from Hafo, a township characterised by poverty with a high crime rate. However, in spite of these factors school inspectors and advisory teachers perceive the school to be successful. The school uses an abundance of energy and unusually high levels of human effort in a very focused way to improve the teaching and learning standard. The study found the co-existence of apparently conflicting management and leadership approaches in managing and leading the school. Strict control used in the school to make teachers work hard is an element of classical organisational theory, with its emphasis on span of control or number of workers supervised. Policies with strict rules are in place to create a calm atmosphere and serve as directives for teachers and learners. On the other hand, constructivist approaches "“ such as instructional leadership, transformational leadership, collegial model of management and open systems "“ are also clearly evident in the findings. Instructional leadership is evident in the emphasis on improvement of classroom practice. Elements of transformational leadership are seen in that the principal motivates the teachers and serves as a role model. The school also has some features of the collegial model of management, and can be described as an open system. Thus, by drawing on management and leadership approaches informed by different traditions and philosophies, the school succeeds against severe odds.
Keywords: School management and organization -- Namibia -- Case studies; Educational leadership -- Namibia -- Case studies; Education and state -- Namibia; School discipline -- Namibia; Children with social disabilities -- Education -- Namibia -- Case studies